Ester Prodrugs of Ketoprofen: Synthesis, Hydrolysis Kinetics and Pharmacological Evaluation - Dhokchawle, B. V.; Tauro, S. J.; Bhandari, A. B. (Drug Research, 2016)
The ester prodrugs of ketoprofen with various naturally available antioxidants; menthol, thymol, eugenol, guiacol, vanillin and sesamol have been synthesized by the dicyclohexyl carbodiimide (DCC) coupling method, purified and characterized by spectral data. Further, their, partition coefficients have been determined as well as, hydrolytic studies performed. The synthesized compounds are more lipophilic compared to the parent moieties and are stable in acidic environment, which is a prerequisite for their oral absorption. Under gastric as well as intestinal pH conditions these prodrugs showed variable susceptibility towards hydrolysis. The title compounds when evaluated for anti-inflammatory, analgesic activities and ulcerogenicity, showed improvement over the parent drug.
Keywords: ketoprofen; ester prodrug; dicyclohexyl carbodimide; anti-inflammatory; analgesic; ulcerogenicity